Ведение пациентов с болевыми синдромами на фоне COVID-19 - L. Т. Аkhmedzhanova; T. M. Ostroumova; O. A. Solokha (Неврология, нейропсихиатрия, психосоматика, 2020)
The disease caused by COVID-19 is multi-organ and involves almost all organs and systems. Myalgias and arthralgias and back pain are common symptoms of COVID-19 and can be observed both at the onset of the disease and in the postcoid period. The cause of muscle and joint damage is both systemic inflammation and direct damage by the virus. Musculoskeletal pain can be observed both at the onset of the disease and in the post-COVID period. Traditionally, musculoskeletal pain is treated with NSAIDs, however, the use of this group of drugs in patients with COVID-19 requires caution as to comorbidity and possible complications of viral infection. The article discusses clinical variants and pathogenetic mechanisms of damage of joints and muscles against the background of COVID-19 infection as well as treatment tactics for patients with skeletal muscle syndrome.